Understanding Nephrogenic Systemic Fibrosis - Chopra, Tushar (Hindawi Publishing Corporation, 2012)
Nephrogenic systemic fibrosis (NSF) is a rare and a debilitating disease noted uncommonly in patients with impaired renal function when exposed to low-stability gadolinium-based contrast agents (Gd-CAs). According to experimental studies, cytokines released by the stimulation of effector cells such as skin macrophages and peripheral blood monocytes activate circulating fibroblasts which play a major role in the development of NSF lesions. The presence of permissive factors, presumably, provides an environment conducive to facilitate the process of fibrosis. Multiple treatment modalities have been tried with variable success rates. More research is necessary to elucidate the underlying pathophysiological mechanisms which could potentially target the initial steps of fibrosis in these patients. This paper attempts to collate the inferences from the in vivo and in vitro experiments to the clinical observations to understand the pathogenesis of NSF. Schematic representations of receptor-mediated molecular pathways of activation of macrophages and fibroblasts by gadolinium and the final pathway to fibrosis are incorporated in the discussion.